Spontaneous Recovery of Ruptured Fetal Membranes Before The 20th Gestational Week Resulting in Term Pregnancies - Çelik, Hüsnü; Gürateş, Bilgin; Atılgan, Remzi; Kavak, Burçin (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: To report six cases in which preterm premature rupture of fetal membranes (PPROM) developed before the 20th gestational week and spontaneously recovered ending-up with full term pregnancies. STUDY DESIGN: This study reports six pregnant women who were admitted to our clinic between 1998 and 2003 due to PPROM diagnosis before the 20th gestational week and in whom amniotic fluid flow spontaneously stopped and full-term pregnancies were achieved. Socio-demographic and clinical characteristics of all cases were retrospectively examined. RESULTS: Mean gestational age of the cases was 14.6±2.2 weeks and amniotic fluid leakage stopped within 3.7±1.6 days. Recurrent PPROM was observed in two of those pregnancies at the 26th and 28th gestational weeks. Term pregnancies were achieved in all cases. CONCLUSION: Although prognosis is extremely unfavorable in cases with very early PPROM development, there is the possibility, though weak, of spontaneous recovery and full-term pregnancy. However, the selection of these cases is of utmost importance. Further studies should be conducted for cost-effective determination of case selection criteria.